Efektivitas Penerapan Zakat Produktif Sebagai Upaya Pendistribusian Dana Zakat di Badan Amil Zakat Nasional Kota Jambi - Nazratun Rivolmi Putri; H. Sissah; Rabiyatul Alawiyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to explain the effectiveness of the productive implementation of zakat as an effort to distribute zakat funds in the Jambi City National Zakat Amil Agency. This research uses a qualitative approach with a descriptive method, namely problems that guide researchers to explore and photograph the situation to be researched thoroughly, broadly and in depth. The data collection technique is field research (field research), while the tools used are observation, interviews and documentation. The data analysis used is qualitative descriptive analysis. The results of this research inform that the distribution of productive zakat carried out by BAZNAS Jambi City through the distribution of productive zakat to mustahik in Jambi City has been effective, because it can improve the welfare of mustahik, this is proven by the increase in income of fourteen out of fifteen mustahik people as a whole and one person whose income is fixed.